2019
DOI: 10.1016/j.radi.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing in health professions education: What radiography educators can learn from other disciplines

Abstract: Objectives: Crowdsourcing works through an institution outsourcing a function normally performed by an employee or group of individuals. Within a crowdsource users, known as the crowd, form a community who voluntarily undertake a task which involves the pooling of knowledge resources. A literature review was undertaken to identify how the tool is being used in health professions education, and potential for use in radiography education. Key findings: 17 papers were returned. Literature identified was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…In a narrative literature review of crowdsourcing in healthcare education undertaken by St. John-Matthews et al (2019), 17 empirical studies were returned.…”
Section: The Data Collection Toolmentioning
confidence: 99%
“…In a narrative literature review of crowdsourcing in healthcare education undertaken by St. John-Matthews et al (2019), 17 empirical studies were returned.…”
Section: The Data Collection Toolmentioning
confidence: 99%
“…Mattos et al (2018) argued that the crowdsourcing platform facilitates the open innovation process, which enables the development of a virtual environment that allows sharing internal and external ideas to address new concepts related to products, services, and challenges for troubleshooting. John-Matthews et al (2019) found that crowdsourcing is associated with…”
Section: Literature Reviewmentioning
confidence: 99%
“…El crowdsourcing en salud constituye una forma de recopilar información en tiempo real y permite ofrecer alternativas complementarias a la concepción de políticas gubernamentales e institucionales, (6,7,8) se ha aplicado en diferentes ámbitos en función del diagnóstico, la vigilancia, (9) la nutrición, (5) y la educación. (10,11) Ranard et al (12) identifican cuatro tareas crowdsourcing: resolución de problemas, procesamiento de datos, vigilancia/monitoreo y encuestas, en conjunto demuestran su aplicabilidad para favorecer el proceso de toma de decisiones en línea. (4,13) Entre las ventajas del crowdsourcing destaca que posibilita el acceso a diversos especialistas para la resolución de un problema de investigación, permite optimizar tiempos en los procesos de tomas de decisiones al trabajar en paralelo diferentes especialistas, y permiten obtener soluciones innovadoras que a su vez optimizan costos.…”
Section: Introductionunclassified
“…(4,13) Entre las ventajas del crowdsourcing destaca que posibilita el acceso a diversos especialistas para la resolución de un problema de investigación, permite optimizar tiempos en los procesos de tomas de decisiones al trabajar en paralelo diferentes especialistas, y permiten obtener soluciones innovadoras que a su vez optimizan costos. (11,14,15) Sin embargo, no está exento de desafíos para la gestión, al tener que lidiar con posibles informaciones poco confiables, agendas de trabajos diferentes, individuos con diferentes comportamientos éticos, o mentalidad de turba. (16,17,18,19) A pesar de las limitaciones en su implementación se evidencian buenas prácticas en la industria farmacéutica Rusa, (20) en China para promover la adherencia a la PrEP, (21) para diseñar un paquete de marketing destinado a promover una intervención digital de la Organización Mundial de la Salud (OMS) en salud mental entre adultos jóvenes, (22) en Nigeria con la creación de una aplicación mediante innovación social móvil para la identificación de centros ilegales y en Corba para obtener requisitos de normativas e infracciones.…”
Section: Introductionunclassified